2018
DOI: 10.20961/jdc.v2i2.26282
|View full text |Cite
|
Sign up to set email alerts
|

Growing Developing Civics Literacy Through Saintific Learning Approach Model Using Learning Media Computer Pro Show Gold Application

Abstract: Developing Civic Literacy for a citizen of a young country is a pedagogical mission that must be borne by every educator directed by the 2013 Curriculum through the use of Scientific approaches in various learning activities that require learning media that can arouse students' rational and intellectual thinking ability, namely Audio Visual Media namely a media based on multimedia with computer hardware and run based on software programs namely; Pro Gold Show. Researchers intend to carry out an Action Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another similar study conducted by Murdaning and Hariani (2018) states that the use of children's poem and song media can improve poem writing skills. Fatahillah et al (2018) revealed that the media proshow displays material through audio-visual that can help students' understanding and interest so that learning outcomes increase. Students' understanding of content as a result of enjoyable learning.…”
Section: Resultsmentioning
confidence: 99%
“…Another similar study conducted by Murdaning and Hariani (2018) states that the use of children's poem and song media can improve poem writing skills. Fatahillah et al (2018) revealed that the media proshow displays material through audio-visual that can help students' understanding and interest so that learning outcomes increase. Students' understanding of content as a result of enjoyable learning.…”
Section: Resultsmentioning
confidence: 99%